2008
DOI: 10.1002/jemt.20587
|View full text |Cite
|
Sign up to set email alerts
|

Hibernation as a far‐reaching program for the modulation of RNA transcription

Abstract: In eukaryotic cells, pre-mRNAs undergo several transformation steps to generate mature mRNAs ready to be exported to the cytoplasm. The molecular and structural apparatus for mRNA production is generally able to promptly respond to variations of metabolic demands. Hibernating mammals, which periodically enter a hypometabolic state, represent an interesting physiological model to investigate the adaptive morpho-functional modifications of the pre-mRNA transcriptional and processing machinery under extreme metab… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
32
0

Year Published

2010
2010
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 26 publications
(35 citation statements)
references
References 37 publications
3
32
0
Order By: Relevance
“…2b and Table 3). The presence of nuclei containing structural components in response to the hibernating phenotype has also been observed in the hazel dormouse (Muscardinus avellanarius) and the edible dormouse (Glis glis) (Malatesta et al 1994(Malatesta et al , 1999(Malatesta et al , 2001(Malatesta et al , 2008; however, the ground squirrel subnuclear structures presently described appear as single foci/nucleus with distinct characteristics, including size. Since nuclear TIA-1 and TIAR perform a range of functions including rendering mRNA translationally silent, modulating the rates of gene transcription, and regulating constitutive and alternative pre-mRNA splicing (Förch et al 2001;López de Silanes et al 2005;Suswam et al 2005), further studies were performed in order to better understand the function of subnuclear foci during torpor.…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…2b and Table 3). The presence of nuclei containing structural components in response to the hibernating phenotype has also been observed in the hazel dormouse (Muscardinus avellanarius) and the edible dormouse (Glis glis) (Malatesta et al 1994(Malatesta et al , 1999(Malatesta et al , 2001(Malatesta et al , 2008; however, the ground squirrel subnuclear structures presently described appear as single foci/nucleus with distinct characteristics, including size. Since nuclear TIA-1 and TIAR perform a range of functions including rendering mRNA translationally silent, modulating the rates of gene transcription, and regulating constitutive and alternative pre-mRNA splicing (Förch et al 2001;López de Silanes et al 2005;Suswam et al 2005), further studies were performed in order to better understand the function of subnuclear foci during torpor.…”
Section: Discussionmentioning
confidence: 98%
“…Instead, TIAR in the nucleus during hibernation may be related to other tasks such as regulating mRNA processing and/ or enhancing mRNA stability, which are also functions associated with TIA-1 and PABP-1 activity (MinvielleSebastia et al 1997;Afonina et al 1998;Förch et al 2001;Suswam et al 2005). In this capacity, nuclear TIA proteins and PABP-1 may represent the inhibition of mRNA processing and, in hibernating hazel dormice, the accumulation of pre-mRNAs at the splicing/cleavage stage has been demonstrated (Malatesta et al 2008). It should be noted, however, that some level of active premRNA processing may be critical during torpor since a small subset of genes are selectively activated in order to support the torpid phenotype.…”
Section: Discussionmentioning
confidence: 99%
“…32,75 Upon arousal, these changes are reversed. For hibernating mammals, they must lower their body temperature from nuclear poly(A) RNAs.…”
Section: Discussionmentioning
confidence: 99%
“…Electron microscopy revealed condensed coiled bodies and amorphous bodies in nucleoplasm during torpor as well as changes in the shape of nucleoli (Malatesta et al, 1994;Malatesta et al, 1999); these disassembled during arousal (Malatesta et al, 2001). Tissue-specific differences in pre-mRNA handling were also apparent; hepatocytes showed a preferential accumulation of premRNAs at the splicing stage whereas brown adipocytes stored these at the cleavage stage (Malatesta et al, 2008). They suggested that storage at the cleavage stage could allow for immediate renewal of translation which fits with the need for the rapid activation of brown adipose metabolism to support thermogenesis that must begin instantly when arousal starts.…”
Section: Reviewmentioning
confidence: 99%